Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1186/s12903-016-0318-5
|View full text |Cite
|
Sign up to set email alerts
|

Oral-health-related background factors and dental service utilisation among Sudanese children with and without a congenital heart defects

Abstract: BackgroundSudanese children with congenital heart defects (CHDs) were found to have poorer oral health than those without CHDs. The aims of this study were to: describe the patterns of oral-health-related background factors in children with and without CHD and explore any differences, and to evaluate the effects of background factors on caries and gingivitis prevalence and dental services utilisation.MethodsIn this analytical cross-sectional study, caregivers of children aged 3–12 years with (CHD cases n = 111… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 37 publications
(50 reference statements)
4
32
0
Order By: Relevance
“…In another recent study in Sudan, a significantly higher prevalence of caries and gingivitis among children aged 3-12 years with a CHD than among those without a CHD, was found (16). The role of the caregiver of a child with a CHD, in terms of practicing daily oral health activities and possessing oral health knowledge, has been recognized to be a risk factor of great importance (1,16,25).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…In another recent study in Sudan, a significantly higher prevalence of caries and gingivitis among children aged 3-12 years with a CHD than among those without a CHD, was found (16). The role of the caregiver of a child with a CHD, in terms of practicing daily oral health activities and possessing oral health knowledge, has been recognized to be a risk factor of great importance (1,16,25).…”
mentioning
confidence: 99%
“…Some studies on the dental knowledge and attitudes of children with a CHD and their caregivers have yielded unsatisfactory results with regard to oral hygiene practices and the use of dental services (7,(16)(17)(18)(19). A study conducted in Brazil in 2002 found that 28.8% of children with a CHD had never visited a dentist (16,20).…”
mentioning
confidence: 99%
See 3 more Smart Citations